BaO-doped silicate and borosilicate glasses for enhanced chemical durability: molecular dynamics simulations based strategy for glass design. Issue 11 (10th August 2022) - Sahu, Pooja; Ali, Sk. Musharaf
Abstract : Effect of BaO doping on the structural modification and its impact on the important properties of binary BaO–SiO2 and ternary Ba-NBS glasses using molecular dynamics (MD) simulations. Abstract : Using the advantageous effect of BaO doping in sodium borosilicate (NBS) glass for nuclear waste immobilization, the structural modification and its impact on the important properties of binary BaO–SiO2 and ternary Ba-NBS glasses were investigated using molecular dynamics (MD) simulations. Significant change in short range and intermediate range order of glass were captured by radial distribution function, coordination number, bond/angle distribution profiles, structure factor, and probability of linking different structural motifs. The order of network connection with higher occurrence of Ba–Si than Ba–B as well as higher Ba–BO4 connectivity than Ba–BO3 demonstrate that the doped Ba ions are less prone to leach out of the glass when exposed to an aqueous environment. Besides, increasing the Si–B4/Si–B3 ratio with an increase in the BaO concentration illustrated that the hydrolysis of glass will slow down with increasing concentration of Ba 2+ ions in the glass matrix. The effect of microscopic structural modification on the macroscopic properties of Ba 2+ -containing glasses was analyzed in terms of mechanical strength, thermal stability, vibrational characteristics (VDOS), and chemical durability. The results disclose the BaO introduced network disruption of glass, which would facilitate the easier incorporation of radionuclides of high-level waste in vitrified glass. Moreover, BaO doping was found to make glass synthesis easier by reducing the glass transition temperature of the base glass matrix. However, BaO caused the loosening of the glass network, which weakens the mechanical strength of glass. Advantageously, the results predict that BaO doping in the NBS glass matrix would strengthen the chemical resistivity of the glass, as tested from a series of computational experiments for Na ion aggregation, ring size distribution, glass surface structure, and ion dissolution while in contact with aqueous solution. It has been demonstrated that the BaO-doped glass will be chemically more durable and would be less likely to degrade when exposed to the aqueous environment. Essentially, the elucidations from macroscopic glass properties have been provided in terms of microscopic understanding. The present findings will ignite further MD simulations and experiments to disclose more interesting microstructure and dynamics due to the presence of BaO in the multicomponent glass matrix.